A comparative analysis of the goal orientation and test anxiety of high school students with and without private tutors - O. Cayubit, Ryan Francis; P. Bactung, Zynnclyrr; A. Gualberto, Lorraine; S. Itom, Vanna Natalie; C. Morales, Sarah Grace; D. Penoliar, Lois Gaiana; S. Sy, Francine Germaine (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of the study was to find out whether the goal orientation and test anxiety of high school students engaged in shadow education will be different from those whose only source of learning is that of mainstream education. A total of 387 high school students participated in this comparative research. They completed the Patterns of Adaptive Learning Scales and the Test Anxiety Inventory and results show that high school students without exposure to shadow education are more mastery-oriented while those with those with private tutors are more performance-oriented. In terms of test anxiety, it appears that those engaged in shadow education are more anxious about the testing process as compared to those without private tutors. Specifically, significant differences between the two groups were observed in their mastery orientation, level of emotionality and total test anxiety.